Pengaruh Persepsi Petani dan Pengaruh Sosial Terhadap Peningkatan Kinerja Usahatani Melalui Adopsi Financial Technology di Kecamatan Cikajang Kabupaten Garut - Benyamin, Gamaliel; Karyani, Tuti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The horticulture sector is one of the sectors that plays an important role in national economic development. Cikajang District, Garut Regency, is one of the centres of horticultural crop production in West Java due to its favourable geographical conditions. Capital is a common problem for farmers, especially farmers with a small farming scale. One of the reasons is the difficulty of farmers in accessing capital sources. Financial Technology comes as a solution for farmers to facilitate access to capital sources. This study aims to describe and analyse thedirect andindirecteffects of farmers' perceptions and social influence on farm performance through the adoption of financial technology as an intervening variable. The research was conducted in Cikajang District, Garut Regency with 72 farmers as respondents. The research method used was Structural Model Equation - Partial Least Square (SEM - PLS) with SmartPLS 4 software. The results showed that farmers' perceptions had no direct effect on improving farm performance, but had an indirect effect on farm performance through the adoption of financial technology. Social influence itself has both a direct and indirect effect on farm performance. The test also found that the adoption of financial technology has a significant effect on farm performance.